Soybean Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2003)
This publication provides estimated cost and returns for forward farm planning for soybeans in south central Kansas.
MF2156_2003_10
Keywords: MF2156; Crops; Economics; MF